Integrated sustainable urban water, energy, and solids management achieving triple net-zero adverse impact goals and resiliency of future communities - Novotny, Vladimir 1938- (John Wiley & Sons, Inc., 2020)
"This book defines the new paradigm of integrated sustainable water, energy, and solids management in future cities, and proves its implementation will reduce greenhouse gas emissions to net zero, provide better water quality of fresh and reclaimed water, and diminish the need for landfills. It advocates for the integration of municipal solid waste as a source of energy that recovers vital resources such as fertilizers. This paradigm is implemented through the conservation, recycling, and generation of blue and green energy, including solar and wind power, and the switch to hydrogen as an energy source through indirect gasification of municipal solid waste. Vladimir Novotny's 50 years of teaching and research culminates in this must-have reference that offers architects, engineers, and planners a methodology for building resilient cities of the future that can withstand natural and anthropogenic disasters"--